1999
DOI: 10.1046/j.1439-0434.1999.147002071.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizoctonia solani Isolates from Tobacco Fields Related to Anastomosis Groups 2-1 and BI (AG 2-1 and AG BI)

Abstract: Tobacco has been reported to be infected by Rhizoctonia solani isolates belonging to anastomosis groups 1 through to 5. Ten pathogenic isolates of the fungus were collected from tobacco fields in Italy and France that anastomosed in high frequencies with AG BI tester isolates and in low frequencies with tester isolates of all described subgroups of AG2, although morphology and thiamine requirement of the isolates were similar to AG 2‐1. Biomolecular evaluations by means of electrophoresis of polygalacturonase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Multiple AGs of R. solani are pathogenic on tobacco (Shew and Melton 1995;Nicoletti and Lahoz 1995;Gutierrez et al 1997;Nicoletti et al 1999;Zhao et al 2013). AG 1, AG 2-1, AG 2-2 and AG 4 cause root rot, stem rot or sore shin, and damping-off, while AG 2-1 and AG 3 cause target spot on leaves of tobacco (Shew and Melton 1995;Gutierrez et al 1997;Nicoletti et al 1999;Mercado Cárdenas et al 2012;Zhao et al 2013). In our study the R. solani isolates identified as AG 2-1 were obtained from plants with damping-off, target spot and sore shin symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple AGs of R. solani are pathogenic on tobacco (Shew and Melton 1995;Nicoletti and Lahoz 1995;Gutierrez et al 1997;Nicoletti et al 1999;Zhao et al 2013). AG 1, AG 2-1, AG 2-2 and AG 4 cause root rot, stem rot or sore shin, and damping-off, while AG 2-1 and AG 3 cause target spot on leaves of tobacco (Shew and Melton 1995;Gutierrez et al 1997;Nicoletti et al 1999;Mercado Cárdenas et al 2012;Zhao et al 2013). In our study the R. solani isolates identified as AG 2-1 were obtained from plants with damping-off, target spot and sore shin symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers further pointed out the diversity of AG-2-1 isolates (Salazar et al 1999;Schneider et al 1997;Pannecoucque and Höfte 2009). Nicoletti et al (1999) reported Nt-isolates as a pathogen of leaf spot of tobacco and other rotation crops including sweet pepper in Italy. Their isolates had a high anastomosis frequency with tester isolates of AG-2 BI (formerly AG-BI; Carling et al 2002), although the morphology and thiamine requirement of the isolates were similar to AG-2-1.…”
Section: Discussionmentioning
confidence: 99%
“…Como critério adicional para identificar os subgrupos de anastomose dos isolados multinucleados AG2, eles foram avaliados quanto ao requerimento para tiamina, conforme Nicoletti et al (1999): discos de cultivo em meio ágar-água foram retirados das margens da colônia e repicados para meio líquido Czapek-Dox (Dhingra & Sinclair, 1995), suplementado ou não com 5 mg/L de tiamina hidroclórica. Aos 10 dias de incubação, a 27 ºC, retirou-se o micélio, removeu-se o excesso de água em papelfiltro, mantido em funil de Büchman, sob vácuo, e pesou-se a massa micelial.…”
Section: Identificação Do Grupo De Anastomoseunclassified